Efficacy of bright light therapy in perinatal depression: A randomized, double-blind, placebo-controlled study - DÖNMEZ, MELİKE; TOPÇUOĞLU, VOLKAN; YORGUNER, NEŞE (My University, 2022)
Background: Uncertainties and difficulties associated with the current treatment modalities for perinatal depression (PND) may cause some mothers to avoid treatment. Raising awareness about the effectiveness and safety of bright light therapy (BLT) may help to alleviate the challenges of PND. The main goal of this study was to evaluate the efficacy and safety of BLT versus placebo in PND.& nbsp;Method: A total of 30 women who were either pregnant or in first year postpartum and diagnosed with major depressive disorder were enrolled; 23 completed the study. Patients were randomly assigned to either the BLT (10,000 lux) or placebo ( .05) in terms of treatment-related side effects. The main limitation of this study is its small sample size, which limits the generalizability of the study\"s findings.& nbsp;Conclusion: The results indicate that BLT is more effective than placebo and is reliable in terms of side effects in PND patients. In order to expand the use of BLT in PND, new studies with larger sample sizes are needed.
Keywords: Sağlık Bilimleri; Health Sciences; Psikiyatri; Klinik Tıp (MED); PSYCHIATRY; Clinical Medicine (MED); Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Psychiatric Mental Health; Psychiatry and Mental Health; Antepartum depression; Bright light therapy; Chronobiology; Perinatal depression; Postpartum depression; SEASONAL AFFECTIVE-DISORDER; POSTPARTUM DEPRESSION; NONSEASONAL DEPRESSION; SLEEP; WOMEN; MOOD; PREGNANCY; RHYTHMS; TRIAL; Antepartum depression; Postpartum depression; Perinatal depression